ANALISIS PENYALURAN DAN PENGGUNAAN DANA DESA DI DESA LINELEAN KECAMATAN MODOINDING KABUPATEN MINAHASA SELATAN - Langkun, Pretty A.; Ilat, Ventje; Pusung, Rudy J. (Universitas Sam Ratulangi, 2019)
Village Funds are APBN funds allocated to Villages transferred through district / city APBD and prioritized for the implementation of development and empowerment of rural communities. The granting of village funds is carried out in stages, namely budgeting, allocation, distribution, use, reporting and monitoring / evaluation of Village Funds. This study aims to determine the mechanism of Village Funds Distribution in Linelean village, Modoinding Subdistrict, South Minahasa Regency, and find out the Use of Village Funds in Linelean Village, Modoinding District, South Minahasa Regency. This research method uses descriptive method and the type of research used is descriptive qualitative. The results showed that the Village Fund Distribution in the village of Linelean was in accordance with the Regulations of the South Minahasa Regent and the Use of Village Funds went well.